Effect of ultrasonic and Nd: Yag laser activation on irrigants on the push-out bond strength of fiber post to the root canal - Funda Fundaoğlu Küçükekenci; Ahmet Serkan Küçükekenci
Abstract Objective: This in vitro study aimed to compare the efficacy of irrigants using various irrigation activation methods to the push-out bond strengths of fiber post to root canal luted with self-adhesive resin cement (SARC). Methodology: Forty-eight decoronated human canines were used. The specimens were divided into four groups corresponding with the post-space irrigation process and were treated as follows: distilled water (DW) (Control) group received 15 mL of DW; sodium hypochlorite (NaOCl)+ethylenediaminetetraacetic acid (EDTA) group was treated with 5 mL of 5.25% NaOCl, 5 mL of 17% EDTA, and 5 mL of DW; passive ultrasonic irrigation (PUI) group was treated with 5 mL of 5.25% NaOCl, 5 mL of 17% EDTA, and 5 mL of DW, and each irrigant was agitated with an ultrasonic file; and laser activated irrigation (LAI) group was treated with 5 mL of 5.25% NaOCl, 5 mL of 17% EDTA, and 5 mL of DW, and each irrigant was irradiated with Nd: YAG laser. Fiber posts were luted with SARC, and a push-out test was performed. Data was analyzed using one-way analysis of variance and Tukey HSD test. Results: The bond strength values for the groups obtained were as follows: Control (10.04 MPa), NaOCl+EDTA (11.07 MPa), PUI (11.85 MPa), and LAI (11.63 MPa). No statistically significant differences were found among all experimental groups (p>0.05). The coronal (12.66 MPa) and middle (11.63 MPa) root regions indicated a significantly higher bond strength compared with the apical (9.16 MPa) region (p<0.05). Conclusions: Irrigant activation methods did not increase the bond strength of fiber post to canal.